2009
DOI: 10.1021/jp809363m
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical SERS at Periodic Metallic Nanopyramid Arrays

Abstract: This paper reports a simple and scalable colloidal templating nanofabrication technology for generating periodic metallic nanopyramid arrays as electrodes for electrochemical surface-enhanced Raman spectroscopy (SERS). These periodic arrays of nanopyramids with nanoscale sharp tips and high tip density can enhance the local electromagnetic field in the vicinity of the nanotips, resulting in high SERS enhancement (on the order of 10 6 ). The effect of the applied electrode potential and the electrode redox reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
45
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 44 publications
2
45
0
Order By: Relevance
“…One example is nanosphere lithography, in which self-assembled arrays of spheres are used as masks to create regular structures such as discs, pyramids, sphere-segment voids and honeycomb structures of various metals [33,[51][52][53][54]. Other fabrication methods include electron beam lithography [55], focused ion beam methods [56], photolithography [57], and templating followed by electrodeposition [58,59].…”
Section: Direct Ec-sersmentioning
confidence: 99%
See 1 more Smart Citation
“…One example is nanosphere lithography, in which self-assembled arrays of spheres are used as masks to create regular structures such as discs, pyramids, sphere-segment voids and honeycomb structures of various metals [33,[51][52][53][54]. Other fabrication methods include electron beam lithography [55], focused ion beam methods [56], photolithography [57], and templating followed by electrodeposition [58,59].…”
Section: Direct Ec-sersmentioning
confidence: 99%
“…surface features associated with maximum electromagnetic enhancement [60,61]. Recent applications of EC-SERS at templated electrodes include the study of amino acid binding to copper [62], measurement of potential induced changes at biological membranes and biomimetic surfaces [63,64], and adsorption of pyridine [54]. The highly reproducibile enhancement factors associated with templated SERS electrodes makes them particularly suited to quantitative electrochemical detection.…”
Section: Direct Ec-sersmentioning
confidence: 99%
“…18 The surface-enhanced Raman scattering 19 (SERS) spectroscopy is widely used for gaining mechanistic and dynamic information on the electrode interfaces, [20][21][22] amplification of very weak signals generated from single molecules or from ultra short-lived transient species, single molecule detection and trace analysis. Several available reports 23,24 on electrochemical SERS studies indicated more or less success because of non-reproducible SERS signals caused by surface inhomogeneity. To the best of our knowledge, electrochemical SERS studies with microelectrodes have not hitherto been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21] We have developed a scalable bottom-up technique for generating wafer-sized periodic gold nanopyramids with nanoscale tips as an efficient surface-enhanced Raman scattering substrate. [22][23][24] Here we demonstrate that the templated nanopyramids can also be utilized as sensitive SPR sensors for chemical and biological sensing. Finitedifference time-domain ͑FDTD͒ simulation has been conducted to complement the optical measurements.…”
mentioning
confidence: 77%